Effectiveness and safety of first-line bevacizumab plus FOLFIRI in elderly patients with metastatic colorectal cancer: Results of the ETNA observational cohort. Issue 3 (May 2016) - Rouyer, Magali; Fourrier-Réglat, Annie; Smith, Denis; Becouarn, Yves; Guimbaud, Rosine; Tubiana-Mathieu, Nicole; Robinson, Philip; Jové, Jérémy; Grelaud, Angela; Noize, Pernelle; Moore, Nicholas; Ravaud, Alain
Abstract: Objectives: Effectiveness of bevacizumab for metastatic colorectal cancer in elderly patients has been investigated in observational studies, mainly associated with oxaliplatin-based regimens. Here, using the ETNA cohort in which the majority of patients received bevacizumab + FOLFIRI, the effectiveness of this combination in elderly patients is explored. Materials and Methods: Patients initiating first-line therapy with bevacizumab between January 2006 and December 2007 were identified in 28 French centres and followed for 24 months. Vital status was collected over 36 months. In the present analysis those who received FOLFIRI were retained (85% of those included), and patients were stratified by age (< 70/≥70 years). The Kaplan–Meier method estimated progression-free survival (PFS) and overall survival (OS), and Cox models were used to assess the independent effect of age on survival outcomes. Results: Among the 351 patients who received bevacizumab + FOLFIRI, 33.9% were aged ≥ 70 years, 66.1% < 70 years. Respectively 15.1% and 9.5% of patients had ECOG-PS ≥ 2; 49.6% and 40.1% used 'stop-and-go' treatment scheduling; and 56.3% and 44.4% experienced grade 3/4 adverse events. Overall response rate was 58.8% and 62.5%. Median [95% confidence interval, CI] OS was respectively 24.1 [20.4; 26.2] and 28.5 [25.0; 31.0] months; age ≥ 70 years and ECOG-PS ≥ 2 were significantly associated with death. Median PFS [95% CI] was respectively 10.9 [9.4; 12.6] and 9.8 [9.2; 11.2] months; hepatic metastases was associated with progression, and age ≥ 70 years was associated with progression after 14 months of follow-up but not before. Conclusions: The present study adds to the literature on the safe and beneficial effect of bevacizumab in the elderly receiving FOLFIRI regimen.